Visual Programming with Recursion Patterns in Interaction Nets - Mackie, Ian; Sousa Pinto, Jorge; Vilaca, Miguel (Electronic Communications of the EASST, 2007)
In this paper we propose to use Interaction Nets as a formalism for Visual Functional Programming. We consider the use of recursion patterns as a programming idiom, and introduce a suitable archetype/instantiation mechanism for interaction agents, which allows one to define agents whose behaviour is based on recursion patterns.